Global volatile signature and polyphenols patterns in Vespolina wines according to vintage - Bordiga, Matteo (2022)
The global volatile signature of Vespolina wines from different vintages was established using solid-phase microextraction combined with gas chromatography–mass spectrometry (HS-SPME/GC-qMS). Wines were also characterised in terms of bioactive compounds (such as individual polyphenols, biogenic amines and their precursors) by high-performance liquid chromatography (RP-HPLC). In addition, some physic ochemical parameters, such as the total phenolic content, total tannins and antioxidant capacity, were evaluated. Seventy-one volatile compounds and thirty-three bioactive compounds were identified in Ves polina wines. The application of multivariate analysis to the obtained data revealed that 2-phenylethyl acetate, ethyl nonanoate, 2-hexanol, isoamyl octanoate and ethyl 2-hydroxymethylbutanoate were the pri mary compounds responsible for Vespolina wines classification, mainly indicative for wines of 2015 and 2013 vintages. Conversely, wines from 2008 and 2009 vintages showed highest values of procyanidin B1, catechin, gallic acid, trans-piceid and trans-resveratrol.